Analisis Pengalaman Pengguna pada Aplikasi Mobile Booking Hotel dengan menggunakan Metode User Experience Questionnaire (UEQ) (Studi pada RedDoorz dan Airy) - Mochammad Alif Kresnanto; Buce Trias Hanggara; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The development of information technology is always experiencing rapid development from year to year. The many facilities that are caused by the development of information technology directly impact on daily activities. One sector that is impacted is the hotel business. Where some developers began to develop applications that aim to facilitate users in booking hotels. Two of these applications are RedDoorz and Airy. In a review given by the user on each application shows a variety of responses from users where there are positive responses and negative responses. the purpose of this research is to know the quality of each application using the User Experience Questionnaire (UEQ) method where this method is used to assess the quality of a product or application based on the impressions of users when using a product or application. UEQ has six rating scales including attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. In this research respondents have different backgrounds with age ranges from 18 years to 34 years who have already used one of the two applications. The results of the analysis using UEQ revealed that Airy obtained better scores on some scales in UEQ than RedDoorz.